The Influence of Job Satisfaction and Self-Efficacy on Employee Performance Through Organizational Commitment as an Intervening Variable - Ike Meilisa Putri; Abdul Rohman; Rochmawati Daud (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to test the effect of HR competence, utilization of accounting information technology, good governance, and internal supervision on the quality of financial reports. The object of this study is the Employees of the Regional Apparatus Organizations of South Sumatra Province. By using the purposive sampling method, the number of samples in this study was 25 regional apparatus organizations with a total of 100 respondents. The independent variables are HR competence, utilization of accounting information technology, good governance, and internal supervision. Meanwhile, the dependent variable used is the quality of financial reports. This study uses a quantitative approach with the type of data in the form of primary data. The testing of this study uses the t-test (Partial) and F Test (Simultaneous) with the SmartPLS Version 4 analysis tool. The results of the study indicate that HR competence, utilization of accounting Information Technology, good governance, and internal supervision have a significant positive effect on the quality of financial reports.